Enhanced Optical and Electrical Properties of Polymer‐Assisted All‐Inorganic Perovskites for Light‐Emitting Diodes. Issue 40 (17th August 2016) - Ling, Yichuan; Tian, Yu; Wang, Xi; Wang, Jamie C.; Knox, Javon M.; Perez‐Orive, Fernando; Du, Yijun; Tan, Lei; Hanson, Kenneth; Ma, Biwu; Gao, Hanwei
Abstract : Highly bright light‐emitting diodes based on solution‐processed all‐inorganic perovskite thin film are demonstrated. The cesium lead bromide (CsPbBr3 ) created using a new poly(ethylene oxide)‐additive spin‐coating method exhibits photoluminescence quantum yield up to 60% and excellent uniformity of electrical current distribution. Using the smooth CsPbBr3 films as emitting layers, green perovskite‐based light‐emitting diodes (PeLEDs) exhibit electroluminescent brightness and efficiency above 53 000 cd m −2 and 4%: a new benchmark of device performance for all‐inorganic PeLEDs.